(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Wesmaelius (s. str.) concinnus (Stephens) is recorded for the first time from Italy on the basis of one specimen collected in Valtellina (Italian Alps). The wings and the morphology of the female terminalia of this species are illustrated.